THE INFLUENCE OF ECOSYSTEMIC FACTORS ON BLACK STUDENT TEACHERS’ PERCEPTIONS AND EXPERIENCE OF EARLY CHILDHOOD EDUCATION - Hannaway, Donna; Steyn, Miemsie; Hartell, Cycil (South African Journal of Higher Education, 2016)
The low enrolment and pass rate of Black students motivated this study to explore how the ecosystemic factors influenced Black student teachers’ perceptions and experiences of ECE at a former white university. This study aimed to understand Black student teachers’ perceptions and experiences of ECE, to provide recommendations to strengthen the ECE programme to meet the needs of the Black students it serves and finally the insight gained addressed the need to recruit and retain Black students. Qualitative research methods such as “photo voice” (Olivier, Wood & De Lange 2009), narratives and semi-structured interviews were conducted and examined through the theoretical lens of Bronfenbrenner’s ecological theory. Initial analysis of the data revealed several categories, such as perceptions of career, status and programme; financial implications; support; and current experiences. Thereafter, further interpretation of the data explicated the following themes: ‘history’, ‘it’s all about money’, ‘community’, ‘cultural relevance’ and ‘me, myself and others’. KEYWORDS: Black student teachers, ecosystemic factors, Early Childhood Education, experiences, perceptions, former white university